2022
DOI: 10.3390/electronics11162476
|View full text |Cite
|
Sign up to set email alerts
|

Booking Public Charging: User Preferences and Behavior towards Public Charging Infrastructure with a Reservation Option

Abstract: Electric vehicles offer a means to reduce greenhouse gas emissions in passenger transport. The availability of reliable charging infrastructure is crucial for the successful uptake of electric vehicles in dense urban areas. In a pilot project in the city of Hamburg, Germany, public charging infrastructure was equipped with a reservation option providing exclusive access for local residents and businesses. The present paper combines quantitative and qualitative methods to investigate the effects of the newly in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
3
1
Order By: Relevance
“…This study comprehensively designs the configuration of charging facilities from the perspectives of charging cost, utilization rate of charging facilities and satisfaction rate of charging demand, so as to meet the charging demand of EV users, avoid idle charging piles as much as possible and reduce the waste of initial investment and later maintenance cost. Notably, the utilization rate of the charging facilities of the configuration scheme in this study can reach 28.94% when the design period is 10 years, surpassing that of previous research [45,46]. Additionally, the satisfaction rate of the charging demand of the configuration scheme in this study is 97.48%, which is also superior to previous research results [50,51], demonstrating its ability to effectively meet the growing charging demand of EV users.…”
Section: Indicator Comparisoncontrasting
confidence: 55%
“…This study comprehensively designs the configuration of charging facilities from the perspectives of charging cost, utilization rate of charging facilities and satisfaction rate of charging demand, so as to meet the charging demand of EV users, avoid idle charging piles as much as possible and reduce the waste of initial investment and later maintenance cost. Notably, the utilization rate of the charging facilities of the configuration scheme in this study can reach 28.94% when the design period is 10 years, surpassing that of previous research [45,46]. Additionally, the satisfaction rate of the charging demand of the configuration scheme in this study is 97.48%, which is also superior to previous research results [50,51], demonstrating its ability to effectively meet the growing charging demand of EV users.…”
Section: Indicator Comparisoncontrasting
confidence: 55%
“…In some studies, the aim was to investigate which actions can improve access to charging and users' perceptions of charging infrastructure as available, reliable, and sufficient for their needs. A pilot experiment on dedicated neighborhood charging [70] showed that potential EV users consider parking-combined and bookable charging options within the city to be of paramount importance, especially as parking is a problem common to both EV users and non-EV users. A survey of stated preferences without a private residential charging option found that the most important aspects of public charging are closely related to personal safety and proximity to one's home, especially if the service is used overnight [71].…”
Section: Socio-demographic and Psychological Aspectsmentioning
confidence: 99%
“…The last group may be more sensitive to the scarcity of other parking opportunities and mostly consists of drivers who rely on charging using public infrastructure. Indeed, a pilot experiment on dedicated neighborhood charging showed that potential users of electric vehicles value charging options combined with parking and spaces bookable within the city, especially because parking is a problem experienced by users of both electric and non-electric vehicles [70].…”
Section: Socioeconomic Cultural Environmental and Experiential Factorsmentioning
confidence: 99%
See 1 more Smart Citation